Loss of earning capacity: Judicial discretion vs. the Civil Law Act 1956 - Mahdzir, Nazli (2011)
The introduction of section 28A by the Civil Law (Amendment)Act 1984 (Act 602) on 1st October 1984 bring with it a married of issues pertaining to the award for loss of earning.While the section itself is simple enought to understand, the interpretation given to it by the judges is not similarly straight forward.The decision in Dirke Peiternella Halma v Mohd Noor bin Baharom & Ors [1990] 3 MLJ 103 and Tan Kim Chuan & Anor v Chandu Nair [1991] 1 MLJ 42 which dealt with the issue of the award for loss of earning capacity, raises the issue that the 1984 amendment had imposes several conditions to an otherwise an area reserved to the judges discretion.Where previously the judges have the discretion in awarding and assessing the award according to the principle of Common Law, these two Supreme Court cases held that the discretionary power of judges to award damages for loss of earning capacity to persons who are not earning at the time of accident was swipe away by section 28A (2)(c) of the Act.This paper attempt to address the question of whether the introduction of section 28A (2) has removed the discretionary power of judges in assessing the award for loss of future earning capacity by subjecting the award and the assessment of this head of damages to the same conditions and fixed multiplier as the award for loss of future earning.